Adobe premiere pro CS6 : classroom in a book : the official training workbook from adobe systems. - Adobe Press (San Jose, Calif. : Adobe Systems Incorporated, 2013)
Provides step-by-step training for using Adobe Premiere Pro CS6 video editing software.
Includes index.
Adult
Adult
System requirements for PC and Mac stated on book.
Keywords: Adobe Premiere; Adobe Premiere; Digital video -- Editing -- Data processing; Digital video -- Editing -- Data processing